Problems Faced by Duty to Consult and the Protection of Aboriginal Peoples in Canada - Nancy Kusbayanti; Bayu Kristianto (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
This paper attempts to analyze the problems faced by the duty to consult doctrine. As an implementation of Section 35 of the Constitution Act of 1982, the duty to consult was first used by the Supreme Court of Canada in the case of Haida Nation in 2004. This doctrine was employed five times by the Supreme Court between 2004 and 2010 to resolve disputes on land and its uses between indigenous people and the Canadian government. In 2018, in the case of Mikisew Cree First Nation v. Canada (Governor General in Council), the Supreme Court determined that this doctrine does not apply to the legislature. While welcomed by indigenous people and those fighting for indigenous people's rights, the duty to consult also raises other problems, namely the application of this doctrine and the legal certainty it creates, especially for businesses related to the use of natural resources.